The Holy Spirit in Action: Why Christians Call Him: The Lord and Giver of Life - Francis Joseph Sheed (USA Servant Books, 1981)
A clear and revealing exposition of the Holy Spirit. It is a fresh look at the activity of the Holy Spirit, based on keen spiritual insight and a lifetime of learning by one of the eminent Christian writers of our time. By tracing the ministry of the Holy Spirit through the Old and New Testaments, the life of the Apostles, and into the early Church, the author offers modern Christians a new appreciation of the presence of the Holy Spirit in their everyday lives.
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Theology; Christian theology; Holy Spirit